Modeling, design, and control of inductive power transfer systems - Chen, Shuxin (Nanyang Technological University, 2021)
The concept of wireless power transfer (WPT) has been proposed for more than a hundred years but were not widely spread until the recent decade. With modern technologies, the commercialization of WPT-based products has become practical and is expected to be a new trend, for being safer, more endurance, and more convenient over traditional wired techniques. Among all WPT techniques, inductive power transfer (IPT) is a promising one. Nowadays, the wireless charging feature of most cell phones is realized by IPT. Besides, IPT is also found to be suitable for various applications, such as electrical vehicles, automatic guided vehicles, and medical implants. Despite the bright future, there are numerous challenges to be solved. Meanwhile, the reliability, power density, cost, and efficiency are critical performance factors for IPT systems, where the limits have not yet been reached. Thus, more research works on IPT are necessary and meaningful. This PhD program seeks for possible improvements of IPT systems. The fundamentals and the state-of-art development of IPT have been reviewed. Three essential aspects, i.e., modeling, design, and control, of IPT systems are investigated.